UAVs-Based Photogrammetric Assessment of Runoff Pathway & Hydrological Surcharge for Drainage Planning - Puteri Izrina Ismi; Mohd Fakhrurrazi Ishak; Solahuddin Daud; Zaihasra Abu Talib (International Journal of Sustainable Construction Engineering and Technology, 2026)
Urban areas located on steep terrain are prone to surface water accumulation and drainage failures, often causing property damage during heavy rainfall. Jalan Semambu, Beserah, Kuantan, has experienced slope-related issues, including wall cracks, tilted structures, and inadequate drainage, necessitating a detailed assessment of surface runoff and terrain characteristics. This study aims to evaluate slope conditions, surface water behavior, and drainage performance to support effective water-management strategies for the study area. Unmanned Aerial Vehicle (UAV) photogrammetry was employed to capture an aerial image using the Phantom 4 Pro, which Agisoft Metashape processed to generate high-resolution orthophotos and a digital elevation model (DEM). The DEM enabled mapping of five distinct slopes and derivation of quantitative metrics, including slope dimensions, slope area perimeter, and cut-and-fill volumes. Results revealed a consistent runoff pattern where flow from all slopes converges toward a foothill pond, identified as a hydrological surcharge point, and continues downslope toward residential areas, highlighting critical zones of potential flooding. Based on UAV-derived slope gradients, a proposed improved drainage alignment of 55–70 meters was developed to mitigate runoff-related hazards. This study demonstrates that UAV photogrammetry provides an accurate and efficient method for quantifying terrain-controlled runoff, identifying vulnerable areas, and informing practical solutions for a sustainable drainage solution. The findings underscore the potential of UAV-based terrain analysis as a decision-support tool for urban water-management planning in steep-slope residential environments.